Conjunctival Eosinophilic Masses With Chronic Eosinophilic Pneumonia. Issue 10 (October 2018) - Nagamoto, Takashi; Mizuno, Yoshinobu; Shigeyasu, Chika; Fukui, Masaki; Yamada, Masakazu
Abstract : Purpose: To report a case of ocular findings associated with chronic eosinophilic pneumonia (CEP). Case: A 63-year-old man was referred to the National Institution of Hospital Organization Tokyo Medical Center with bilateral eyelid swelling due to giant papillomatous changes, each measuring approximately 10 mm in diameter with severe hyperemia on the tarsal conjunctiva. He was followed for CEP for 8 years and systemically treated with 6 mg oral prednisolone for an average of 5 years. Because the lesions did not respond to topical 0.1% tacrolimus and 0.025% levocabastine treatment and because an increase in intraocular pressure was found to occur as a side effect of 0.01% betamethasone instillation for several months, we performed surgical resection of the bilateral conjunctival lesions. Histopathological findings revealed extreme eosinophil, plasma cell, and lymphocytic infiltration and interstitial fibrosis. These conjunctival specimen findings were similar to those seen in the alveolar lesions in CEP. Topical antiinflammatory therapy using 0.1% tacrolimus eye drops was administered after surgery, which relieved the patient's lid swelling and itching. However, the lesions concurrently changed to be consistent with exacerbation and remission of systemic CEP. Conclusions: Based on the clinical course and histopathology, the conjunctival proliferative masses in our case were assumed to be associated with CEP.